Members only - Pandya, Sameer (Mariner Books / Houghton Mifflin Harcourt, 2020)
"First the white members of Raj Bhatt's posh tennis club call him racist. Then his life falls apart. Along the way, he wonders: where does he, a brown man, belong in America? Raj Bhatt is often unsure of where he belongs. Having moved to America from Bombay as a child, he knew few Indian kids. Now middle-aged, he lives mostly happily in California, with a job at a university. Still, his white wife seems to fit in better than he does at times, especially at their tennis club, a place he's cautiously come to love. But it's there that, in one week, his life unravels. It begins at a meeting for potential new members: Raj thrills to find an African American couple on the list; he dreams of a more diverse club. But in an effort to connect, he makes a racist joke. The committee turns on him, no matter the years of prejudice he's put up with. And worse still, he soon finds his job is in jeopardy after a group of students report him as a reverse racist, thanks to his alleged anti-Western bias. Heartfelt, humorous, and hard-hitting, Members Only explores what membership and belonging mean, as Raj navigates the complicated space between black and white America."--